(untitled) (Global Journal of Human-Social Science, 2013)
The present essay aims to give both a contribution to rethinking sociology of intellectuals and to the study of transition from the hierarchical order of modernity (idea of Society) to a social pattern based on persons and subjects. In particular, we will try to paint a sketch of the transformations of the intellectual function. Exerted by big bureaucratic machines, today the intellectual action partially detaches itself from the intellectual function carried out by big bureaucratic machines of the modern era. New typologies of intellectuals were born as well as a new, deeply ambivalent public space. The Internet and networked individualism are the main carriers of these transformations.